AI adoption in accounting education: a UTAUT-based analysis of mediating and moderating mechanisms - Han, Mengrong; Mustafa, Hasri; Kharuddin, Saira (Duzce University, Faculty of Education, 2025)
This study investigates the adoption and usage of artificial intelligence (AI) technologies among Chinese undergraduate accounting students, focusing on the roles of Social Influence (SI), Behavioral Intention (BI), and Actual Usage (AU), while examining the mediating effect of BI and the moderating effect of Voluntariness of Use (VOU). By extending the Unified Theory of Acceptance and Use of Technology (UTAUT) model, it addresses gaps in understanding the social and behavioral factors influencing AI adoption within the educational context. A quantitative research design was employed, utilizing Partial Least Squares Structural Equation Modeling. Data was collected through a self-administered survey distributed via the Wenjuanxing platform, with responses from 362 Chinese undergraduate accounting students analyzed to test the hypothesized relationships. The findings reveal that SI significantly affects both BI and AU, with BI serving as a partial mediator in the SI-AU relationship. However, VOU did not exhibit a significant moderating effect on the SI-BI pathway. These results provide insights into the dual role of SI and the importance of fostering positive attitudes toward AI adoption among students. This study contributes to the literature by extending the UTAUT model in an educational setting, emphasizing the interplay of cultural and social dynamics in influencing AI adoption. It offers actionable recommendations for educators, policymakers, and technology vendors to promote AI integration in accounting education and prepare students for AI-driven professional environments.